Pengaruh Pertumbuhan Ekonomi, Industrialisasi, Kepadatan Penduduk, dan Transportasi terhadap Kualitas Udara di Kabupaten/Kota Jabodetabek Tahun 2020-2022 - Syukri, Irfan; Soebijarto, Ekaria (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2025)
Unhealthy air quality is an annual problem that has yet to be resolved in many countries, including Indonesia. The government has made many efforts, especially the Ministry of Environment and Forestry (KLHK), to overcome the low air quality as part of its annual report agenda. However, air quality in DKI Jakarta, Banten, and West Java, especially the Jabodetabek regencies/cities, still needs improvement. That aligns with the conditions in Jabodetabek, which is densely populated and has transportation, high economic activity, and the concentration of industry that has begun to shift from the core area to the buffer zone. Therefore, this study will review the effect of economic growth, industrial agglomeration, population density, and transportation on air quality in Jabodetabek with the Random Effect Model (REM). The results show that increasing industrial agglomeration and population density significantly affect the decreasing of air quality in the Jabodetabek regencies/cities.